(untitled) (Research, Society and Development, 2021)
The present scientific work aims to analyze the disciplinary administrative processes and procedures, with emphasis on what happens within the scope of the Military Police of the State of Tocantins - PMTO, with a view to expanding the military police in charge (1st perfected Sergeants and Sublieutenants of the combatant staff) Investigation and Preliminary Investigation Procedure – PIP. Pursuant to the Federal Constitution of 1988, the administrative disciplinary process is mandatory for investigation of conduct and possible application of penalties. Thus, in the State of Tocantins, through Law n. 2578 (2012), as well as by Decree n. 4994 (2014), which deal with administrative processes to investigate the conduct of state military members. In addition to Normative Instruction No. 001/2014 – Office of the General Commander that instituted the PIP in PMTO. It is noteworthy that administrative disciplinary processes in the military sphere are important for the maintenance of hierarchy and discipline, as it is the basis of Brazilian military institutions. The importance of the PIP, on the other hand, is to investigate the facts that do not have sufficient evidence for the establishment of an Inquiry. In the work methodology, applied, descriptive, bibliographical and documentary research was used, using the hypothetical-deductive method and carried out a qualitative approach. In the end, it was concluded that there is a legal possibility for the aforementioned graduates in the scope of the PMTO to be in charge of investigation and PIP, as long as there is a change in the rules.